2000
DOI: 10.1115/1.1339985
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of a Cause of Backfire and Its Control Due to Crevice Volumes in a Hydrogen Fueled Engine

Abstract: To understand the occurrence of backfire in hydrogen fueled engines using an external (inducted) fuel supply, a fundamental study was completed using a modified experimental engine. A relation was found between the crevice volume in the combustion chamber and the occurrence of backfire. The results showed that the crevice around the spark plug electrode was not a major cause of backfire, but the combustion state of the mixture in the piston top land crevice, second land, and ring groove did have a direct affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…Summing up, it is concluded that the optimal hydrogen enrichment with diesel is 30% [11][12][13][14], which shows that it has less smoke, less particulates emission, a higher brake thermal efficiency and hence a lower specific energy consumption. Hydrogen is used in the dual fuel mode with diesel and shows the highest brake thermal efficiency of 30% at a compression ratio of 24.5:1 [15,16]. The performance of dual injection hydrogen fueled engine by using solenoid in-cylinder injection and external fuel injection technique has also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Summing up, it is concluded that the optimal hydrogen enrichment with diesel is 30% [11][12][13][14], which shows that it has less smoke, less particulates emission, a higher brake thermal efficiency and hence a lower specific energy consumption. Hydrogen is used in the dual fuel mode with diesel and shows the highest brake thermal efficiency of 30% at a compression ratio of 24.5:1 [15,16]. The performance of dual injection hydrogen fueled engine by using solenoid in-cylinder injection and external fuel injection technique has also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these [8,9] address the economic, technical, environmental, and political implications of its implementation, while others focus either on specific technical problems [10,11] or on hydrogen production [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, despite much effort, there exist no guaranteed preventive steps. However, identification of preignition sources, such as in-cylinder hot-spots (Furuhama et al, 1977;Tang et al, 2002), oil contaminants , combustion in crevice volumes (Lee et al, 2001), and residual energy in the ignition system (Kondo et al, 1997), has provided the necessary minimizing steps. These include use of cold-rated spark plugs, low coolant temperature, and optimized fuel-injection timing.…”
Section: Preignition and Knockmentioning
confidence: 99%